2021
DOI: 10.1111/tmi.13664
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the cascade of care for hypertension in Sierra Leone

Abstract: Objective To assess the care for hypertension in Sierra Leone, by the use of a cascade‐of‐care approach, to identify where the need for healthcare system interventions is greatest. Methods Using data from a nationwide household survey on surgical conditions undertaken in 1956 participants ≥18 years from October 2019 to March 2020, a cascade of care for hypertension consisting of four categories – hypertensive population, those diagnosed, those treated and those controlled – was constructed. Hypertension was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 59 publications
2
22
3
Order By: Relevance
“…A study of only low-and middleincome countries found that loss to care was highest at the diagnosis and control stages, with 61% loss and 66% loss, respectively [25]. Studies from Nigeria [26], Sierra Leone [27] and South Africa [11] also show that the greatest loss to care happens at the screening and diagnosis stages, and although the loss to care at the control stage was also high, it did not reach the level observed in the present study. Thus, the high level of loss to care at the control stage is a relatively unique characteristic of this study.…”
Section: Discussioncontrasting
confidence: 90%
“…A study of only low-and middleincome countries found that loss to care was highest at the diagnosis and control stages, with 61% loss and 66% loss, respectively [25]. Studies from Nigeria [26], Sierra Leone [27] and South Africa [11] also show that the greatest loss to care happens at the screening and diagnosis stages, and although the loss to care at the control stage was also high, it did not reach the level observed in the present study. Thus, the high level of loss to care at the control stage is a relatively unique characteristic of this study.…”
Section: Discussioncontrasting
confidence: 90%
“…The study design and age population of 25-65 years used in the STEPs survey make it difficult to compare with our study. In Sierra Leone, a much higher prevalence of hypertension (49.6%) was recently reported in a provincial district by Odland et al, while a lower rate of hypertension (22%) was reported by Geraedts et al when compared to this study [24,26]. The disparity may be attributed to the age differences of the studied cohorts (20 years and above in our study, unlike 40 years and above in the reported study by Orland et al [24]).…”
Section: (Which Was Not Certified By Peer Review)contrasting
confidence: 69%
“…Additional information on the sensitivity and specificity of parameters related to target organ damage is shown in Supplementary Table 1. [22,24,26]. Therefore, our study has contributed critical evidence on the burden and distribution of CMRFs among adults living in an urban setting in SSA.…”
Section: Preclinical Target Organ Damage (Tod) Of the Study Participantsmentioning
confidence: 91%
See 2 more Smart Citations